Plasma Nesfatin-1 and Leptin in pubertal and non-pubertal Murrah buffalo heifers (Bubalus bubalis) (Journal of Advanced Veterinary and Animal Research, 2015)
Buffaloes  mostly  suffer  from  delayed  puberty, anestrus,  subestrus,  summer  infertility,  prolonged inter-calving  interval  and  postpartum  uterine disorders.  Nesfatin-1  and  Leptin  are  directly  or indirectly  related  with  body  weight  (BW),  feed parameters  and  regulation  of  puberty.  The  objective of  this  study  was  to  investigate  the  influence  of Nesfatin-1  and  Leptin  in  pubertal  and  non-pubertal Murrah  buffalo  heifers.  The  Murrah  buffalo  heifers (n=13) were randomly selected and divided into two groups; pubertal group (PG) and non-pubertal group (NG). Heifers with plasma progesterone (P 4 ) level of ?1 ng/mL were classified as PG. Blood samples were collected at fortnight intervals for analysis of plasma Nesfatin-1,  Leptin,  P 4 ,  glucose  and  non-esterified fatty acids. Body weight, dry matter intake and feed conversion  efficiency  were  recorded  at  fortnight intervals.  The  mean  (±SEM)  plasma  Nesfatin-1, Leptin,  P 4 ,  BW  and  feed  conversion  efficiency  (%) were significantly (P